Strengthening Local Democratic Governance through the Evaluation of Campaign Stages and Electoral Institutional Arrangements in Brebes Regency - Achmad Irwan Hamzani (AKM, 2026)
Regional head elections (Pilkada) constitute an essential instrument of local democracy that requires not only administrative success but also the establishment of democratic and integrity-based governance. This activity aimed to evaluate campaign stages, the formation of ad hoc electoral bodies, and the institutional arrangements of Pilkada organizers as part of efforts to strengthen local democratic governance in Brebes Regency. The activity was conducted through a Focus Group Discussion organized by the General Election Commission of Brebes Regency involving resource persons, employing lectures, institutional reflection, and the identification of problems in Pilkada administration. The findings indicate that the implementation of campaign stages continues to face several challenges, including weak political competition due to the phenomenon of single candidates, the tendency toward administrative-oriented campaigns, and the challenges posed by digital campaigning. In addition, ad hoc electoral bodies continue to encounter limitations related to human resource capacity, independence, integrity, and institutional coordination effectiveness. Other challenges include the high workload borne by election organizers and institutional efficiency demands in simultaneous Pilkada implementation. This activity contributes to strengthening institutional reflection, enhancing the professionalism of Pilkada organizers, and formulating recommendations for more participatory, transparent, and integrity-based local democratic governance.